Design of a low harmonic five-level inverter based on a wind power plant using a DC generator with LCL filter - Setiyono Setiyono; Bambang Dwinanto; Dyah Nur’ainingsih (National Research and Innovation Agency, 2026)
Wind energy is one of the green energy sources that can decrease reliance on fossil fuels such as oil and coal. Wind turbines harness the kinetic energy of the wind and transform it into mechanical energy, which is subsequently converted into electrical energy using a DC generator. The generated DC voltage is transformed into AC voltage by an inverter unit. However, conventional inverters generally produce square-wave outputs with high total harmonic distortion (THD), whereas AC power systems ideally require sinusoidal waveforms with low harmonic content. This research proposes the design of a renewable energy–based power supply system capable of generating both DC and AC voltages for low-power applications. The novelty of the proposed system lies in the use of a five-level inverter with fewer switching devices than the cascaded inverter topology, combined with a T-model inductive-capasitive-inductive (LCL) filter to suppress harmonic distortion at the inverter output. The method involves modeling and simulating the system design using MATLAB Simulink. Simulation results show that the five-level inverter produces an output voltage amplitude of 270 V at 50 Hz with a THD of 28.48 %. After applying the LCL filter (L1 = L2 = 0.01 H and C = 1 mF), the THD decreases to 2.56 % for a 10 Ω resistive load, 2.61 % for an RL load (100 Ω, 0.8 mH), and 2.54 % for an RC load (10 Ω, 1 µF). These values comply with the IEEE 519 standard requiring THD below 5 %. Therefore, the proposed system has potential for small-scale renewable energy applications.